2021
DOI: 10.1093/ejcts/ezab143
|View full text |Cite
|
Sign up to set email alerts
|

Native and prosthetic graft infections of the thoracic aorta: surgical management

Abstract: OBJECTIVES Infection of the native aorta or after previous open or endovascular repair of the thoracic aorta is associated with high risks for morbidity and mortality. We analysed the outcome after surgical management of a native mycotic aneurysm or of prosthetic graft infection of the descending aorta. METHODS From June 2000 to May 2019, a total of 39 patients underwent surgery in our centre for infection of the native desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In general, the literature regarding the management of thoracic VGIs is scanty, and most of the available documents are surgical case series or retrospective studies with a limited number of patients [21,64,77,79] . Currently, and as a natural consequence of broader use of TEVAR compared to open repair, infected endografts are more commonly observed and reported [80] . Kahlberg et al [60] studied outcomes for open surgical grafts and endograft infections.…”
Section: Special Situations: Fistula and Partial Graft Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the literature regarding the management of thoracic VGIs is scanty, and most of the available documents are surgical case series or retrospective studies with a limited number of patients [21,64,77,79] . Currently, and as a natural consequence of broader use of TEVAR compared to open repair, infected endografts are more commonly observed and reported [80] . Kahlberg et al [60] studied outcomes for open surgical grafts and endograft infections.…”
Section: Special Situations: Fistula and Partial Graft Resectionmentioning
confidence: 99%
“…Aorto-esophageal (AEF) or aorto-bronchial fistula (ABF) are reported in up to 1.5% of treated patients [80,83] . Czerny et al [84,85] from an international collaboration group found 1.5% AEF and 0.56% ABF.…”
Section: Special Situations: Airway and Esophageal Fistulamentioning
confidence: 99%
“…Defining the location and extent of infection and the status of surrounding tissue is crucial for the subsequent treatment planning. In particular, proper diagnosis of infection limited to the vascular portion of the thoracic aortic grafts (VPI, about 2%) [ 62 ] is critical due to the high mortality associated with replacement of the graft, especially in patients with long-lasting infections or severe co-morbidities. Alternative options such as graft salvage through aggressive debridement and irrigation or non-surgical management with antibiotics alone [ 63 ] can be considered.…”
Section: Wbc Spect/ctmentioning
confidence: 99%